Cell-mediated immune response in goats vaccinated with killed Mycoplasma mycoides subsp. capri saponin vaccines - RANA, RAJNEESH; SRIVASTAVA, N C (The Indian Journal of Animal Sciences, 2014)
The cell-mediated immune response of sonicated M.capri saponin vaccines was studied in goats.Vaccines, viz. vaccine A (1.0 mg protein/dose) and vaccine B (1.5 mg protein/dose) were prepared and inoculated with 1.0 ml of sterile saponIn solution (3.0 mg/ml) in 2 different groups of animals comprising 17 in each group. Vaccine A was better than that of vaccine B as it elicited higher per cent leukocyte migration inhibition (LMI) values while consisting of lesser protein concentration.